Language Learning Strategies Among Student Teachers: Frequency, Specializations, and Pedagogical Implications - Granada, John Matthew Philip Michael (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the language learning strategies (LLS) employed by fourth-year Bachelor of Secondary Education (BSED) students at Negros Oriental State University Main Campus I, with particular attention to the frequency and variation of strategy use across academic specializations. Anchored in Oxford’s (1990) taxonomy of language learning strategies and guided by a descriptive-comparative research design, the study sought to identify the extent to which student teachers utilize direct strategies, memory, cognitive, and compensation, and indirect strategies, metacognitive, affective, and social. A total of 132 respondents from six specializations (English, Filipino, Mathematics, Sciences, Social Studies, and Values Education) participated in the study, with data gathered through the Strategy Inventory for Language Learning (SILL) and analyzed using weighted mean and inferential statistics. The findings revealed that student teachers employ all six categories of language learning strategies at a generally high level, indicating active and strategic engagement in their language learning processes. Among the strategy types, metacognitive strategies emerged as the most frequently used, reflecting strong tendencies toward planning, monitoring, and self-evaluation, followed by cognitive and social strategies that support active language use and interaction. Memory and compensation strategies were also commonly employed, although certain specific techniques within these categories were used only moderately. Affective strategies, while used at a high level overall, showed relatively less variation across indicators, suggesting consistent patterns of emotional regulation among learners. Inferential analysis further demonstrated that significant differences exist in the use of memory, cognitive, compensation, metacognitive, and social strategies when grouped according to specialization, while no significant difference was found in affective strategies. English and Values Education majors consistently reported higher and more varied strategy use, whereas Mathematics and Social Studies majors demonstrated comparatively lower levels in several categories. These results affirm that academic specialization influences learners’ strategic behavior, reflecting the differing linguistic and cognitive demands associated with each discipline. The study underscores the importance of integrating explicit language learning strategy instruction within teacher education programs. In recognizing both the strengths and gaps in students’ strategic practices, educators and curriculum developers can design more responsive and specialization-sensitive interventions that foster learner autonomy, communicative competence, and reflective practice. Ultimately, the findings contribute to a more nuanced understanding of how future teachers engage with language learning and highlight the need to cultivate strategic awareness as a core component of effective teacher preparation.
Keywords: Language Learning Strategies, Pre-Service Teachers, Specialization Differences, English Language Learning